Is it necessary to re-evaluate diagnostic criteria for Wilson disease in children? - Balcı Sezer, Oya; Perk, Peren; Hoşnut, Ferda Özbay; Köse, Serdar Kenan; Özcay, Figen (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: The differential diagnosis of Wilson Disease (WD) is challenging, especially in children, because liver copper levels may also increase in other chronic liver diseases with bile stasis. The aim of this study is to determine urine and liver copper cut-off values to differentiate WD from other chronic liver diseases (non-WD, NWD) in children. Materials and Methods: Seventy-six patients participated in the study, 35 with WD and 41 with NWD. The two groups were divided into two subgroups according to the presence of cholestasis. At the time of diagnosis, age, sex, biochemical test results, serum ceruloplasmin, baseline 24-h urinary copper levels, liver biopsy histological findings, liver copper levels, and Child-Pugh scores were obtained from medical records. Copper content in liver tissue and copper levels in urine were measured by atomic absorption spectrometry. Cut-off values for differentiation of WD from NWD were determined by receiver operating characteristic (ROC) analysis. Results: A liver copper cut-off value of 98 µg/g indicated WD with 91% sensitivity and 65.4% specificity (area under the curve =0.838, 95% CI: 0.749-0.927). A 24-h urinary copper cut-off value of 67.5 µg/24h indicated WD with 85% sensitivity and 71% specificity (area under the curve =0.843, 95% CI: 0.752-0.934). Conclusion: In this study of pediatric chronic liver disease patients, copper cut-off values for distinguishing WD differed substantially from those used for diagnosis. A larger scale study is warranted to re-evaluate liver copper and 24-h urinary copper cut-offs for children with suspected WD.